2005
DOI: 10.1097/01.alc.0000179409.80370.25
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-Level Prenatal Alcohol Exposure Alters Striatal Dopamine System Function in Rhesus Monkeys

Abstract: These results suggest that the vulnerability of the DA system to the effects of moderate doses of alcohol during gestation depend on the timing of the alcohol exposure. Early-gestation moderate alcohol exposure resulted in a reduction or blunting of dopaminergic function in adulthood, whereas middle to late exposure (without early exposure) either induced the opposite pattern or heightened dopaminergic function. Continuously exposed monkeys showed the largest effect, suggesting that the sooner women stop drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 81 publications
3
52
0
Order By: Relevance
“…Moreover, prenatal alcohol exposure in rodents has been shown to alter neurotransmitter functioning, including decreased DA uptake, deficits in serotonin reuptake sites, reduced density of NMDA receptor agonist binding sites, altered DA synthesis, and altered behavioral responses to dopaminergic drugs (Druse et al, 1990;Hannigan & Pilati, 1991;Kim & Druse, 1996;Maier, Chen, & West, 1996;Sutherland, McDonald, & Savage, 1997). Our own work has found that prenatal alcohol exposure contributed to altered DA neurotransmitter function in the striatum depending on the gestational timing of the alcohol exposure (Schneider et al, 2005).Because of the susceptibility of the developing brain to alcohol-induced apoptotic neurodegeneration (Ikonomidou et al, 2000), prenatal alcohol exposure could compromise cortical plasticity and therefore, acquisition of adaptive behavioral responses to environmental events. Both human and animal studies have concluded that prenatal alcohol exposure can disrupt myelination, as well as glial cells, which are critical for neuronal myelin development (Burden et al, 2005;Guerri, Pascual, & Renau-Piqueras, 2001;Sowell et al, 2001).…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…Moreover, prenatal alcohol exposure in rodents has been shown to alter neurotransmitter functioning, including decreased DA uptake, deficits in serotonin reuptake sites, reduced density of NMDA receptor agonist binding sites, altered DA synthesis, and altered behavioral responses to dopaminergic drugs (Druse et al, 1990;Hannigan & Pilati, 1991;Kim & Druse, 1996;Maier, Chen, & West, 1996;Sutherland, McDonald, & Savage, 1997). Our own work has found that prenatal alcohol exposure contributed to altered DA neurotransmitter function in the striatum depending on the gestational timing of the alcohol exposure (Schneider et al, 2005).Because of the susceptibility of the developing brain to alcohol-induced apoptotic neurodegeneration (Ikonomidou et al, 2000), prenatal alcohol exposure could compromise cortical plasticity and therefore, acquisition of adaptive behavioral responses to environmental events. Both human and animal studies have concluded that prenatal alcohol exposure can disrupt myelination, as well as glial cells, which are critical for neuronal myelin development (Burden et al, 2005;Guerri, Pascual, & Renau-Piqueras, 2001;Sowell et al, 2001).…”
mentioning
confidence: 69%
“…The second goal was to examine whether prenatal exposure to alcohol, stress, or both would alter withdrawal responses (aversion) to repeated tactile stimulation in rhesus monkeys. Our studies to date indicate that rhesus infants from both prenatal stressand prenatal alcohol-exposed pregnancies exhibited reduced neonatal orienting and motor maturity (Schneider, 1992;Schneider, Moore, & Becker, 2001;Schneider, Roughton, & Lubach, 1997), increased stress hormone reactivity (Clarke, Wittwer, Abbott, & Schneider, 1994;Schneider, Moore, & Kraemer, 2004), learning deficits (Schneider, Moore, & Kraemer, 2001), and altered striatal DA system function (Roberts et al, 2004;Schneider et al, 2005). …”
mentioning
confidence: 83%
See 3 more Smart Citations